The mother-blame game - Reimer, Vanessa, 1986-; Sahagian, Sarah, 1986- (Demeter Press, 2015)
"The Mother-Blame Game is an interdisciplinary and intersectional examination of the phenomenon of mother-blame in the twenty-first century. As the socioeconomic and cultural expectations of what constitutes "good motherhood" grow continually narrow and exclusionary, mothers are demonized and stigmatized-perhaps now more than ever-for all that is perceived to go "wrong" in their children's lives. This anthology brings together creative and scholarly contributions from feminist academics and activists alike to provide a dynamic study of the many varied ways in which mothers are blamed and shamed for their maternal practice. Importantly, it also considers how mothers resist these ideologies by engaging in empowered and feminist mothering practices, as well as by publicly challenging patriarchal discourses of "good motherhood""--